Ipsilateral Rotational Autokeratoplasty for the Management of Traumatic Corneal Scar - Alime Günes; Tahir Kansu Bozkurt; Cihan Unlu; Betül Ilkay Sezgin Akcay; Hüseyin Bayramlar (Case Reports in Ophthalmological Medicine)
A 40-years-old male patient with a corneal scar secondary to perforating eye injury had undergone ipsilateral rotational autokeratoplasty in our clinics. The corneal scar involved the pupillary area. The patient had a preoperative visual acuity of counting fingers. The patient’s cornea was trephined with a 0.5 mm temporal decentration. The 8.0 mm autograft was rotated approximately 180° to relocate the scar to the temporal aspect of the cornea. The final position of the corneal scar was temporal of the visual axis and central area was clear. The visual acuity at 1-, 3-, and 6-months followups was better than the first visual acuity in the patient. Ipsilateral rotational autokeratoplasty has many advantages over conventional keratoplasty. There is no risk of immunological rejection of the graft, postoperative corticosteroids are not needed as frequently, and donor cornea is not required. A rotational autograft can be a powerful alternative to conventional keratoplasty for some patients with traumatic corneal scars.